PREDICTORS OF TREATMENT RESPONSE OF VASOPROLIFERATIVE RETINAL TUMORS TO RUTHENIUM-106 BRACHYTHERAPY. Issue 12 (December 2016) - Brockmann, Claudia; Rehak, Matus; Heufelder, Jens; Cordini, Dino; Brockmann, Tobias; Corkhill, Caitlin; Joussen, Antonia M.; Hager, Annette
Abstract : Purpose: To identify predictors of treatment response by evaluating long-term outcomes of vasoproliferative retinal tumors after ruthenium-106 brachytherapy. Methods: In a retrospective case series, 39 eyes of 38 patients with vasoproliferative retinal tumors received ruthenium-106 brachytherapy between 2001 and 2013. Baseline clinical and morphologic parameters were analyzed regarding posttreatment tumor activity status. Results: Within a median follow-up period of 2.9 ± 2.9 years, overall, a tumor inactivation was achieved in 72% of cases and visual acuity remained stable in 69%. The mean apex dose was 90 ± 23 Gy (range, 51–140 Gy). Mean tumor thickness decreased significantly, from 2.9 ± 0.9 mm to 1.5 ± 1.0 mm ( P < 0.001; paired t -test). Persistence or recurrence of tumor activity occurred in 28% of cases, requiring secondary intervention with intravitreal drug injections, vitrectomy, cryotherapy, or repeated brachytherapy. Comparison of inactive and active vasoproliferative retinal tumors revealed significant correlation between both initial basal tumour diameter and area and subsequent tumour activity status. In particular, a diameter >7.5 mm was associated with an 8-fold risk of persistent or recurrent activity, whereas basal area >40 mm 2 demonstrated a 6-fold risk ( P = 0.009 and 0.021, respectively; Fisher's exact-test). In contrast, tumor thickness was not found to be of prognostic relevance. Conclusion: Ruthenium-106 brachytherapy is an effective and safe therapeutic option for vasoproliferative retinal tumors. Additionally, tumor diameter and area are efficient predictors of persistence or recurrence of tumor activity. Abstract : Outcome data of 39 eyes with vasoproliferative retinal tumors treated with ruthenium-106 brachytherapy within a follow-up period of 3 years were analyzed. In 72%, tumor inactivation was achieved. Initial basal tumor diameter and area, but not tumor thickness, were revealed as efficient predictors for the persistence or recurrence of tumor activity.